The Influence of GIZTING Video Media on The Knowledge and Behavior of Stunting Toddler Families - Anjani, Amelia Sarah; Adillah, Izzah Kholidatul; Dhuha, Mala Intanin; Wardani, Novita Ika (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2022)
Background: The incidence of short toddlers or commonly referred to as stunting is a chronic nutritional problem because of malnutrition that has accumulated over a long period of time. Chronic malnutrition occurs from infancy in the womb until the age of two. Data on the prevalence of stunting under five collected by the World Health Organization (WHO) shows that Indonesia is included in the third country with the highest prevalence in the Southeast Asia region / South-East Asia Regional (SEAR). Currently the most important thing to reduce the risk of stunting in toddlers is to provide health education to parents through Video GIZTING, where parents with low education generally trigger stunting in children twice as high as parents with higher education.Objective: To give influence of video media